2022
DOI: 10.1002/elsc.202100156
|View full text |Cite
|
Sign up to set email alerts
|

Streamlining of a synthetic co‐culture towards an individually controllable one‐pot process for polyhydroxyalkanoate production from light and CO2

Abstract: Rationally designed synthetic microbial consortia carry a vast potential for biotechnological applications. The application of such a consortium in a bioprocess, however, requires tight and individual controllability of the involved microbes. Here, we present the streamlining of a co-cultivation process consisting of Synechococcus elongatus cscB and Pseudomonas putida for the production of polyhydroxyalkanoates (PHA) from light and CO 2 . First, the process was improved by employing P. putida cscRABY, a strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Francis (2016 10.3389/fmicb.2023.1126032 Frontiers in Microbiology 15 frontiersin.org modest (Löwe et al, 2017;Fedeson et al, 2020). Additional expression of a sucrose porin (cscY) and a sucrose operon repressor (cscR) further improved sucrose utilization (Löwe et al, 2020), while further optimization of the nitrogen-deficiency response pathway (Hobmeier et al, 2020) and culture conditions could boost PHA titer further (Kratzl et al, 2023; Table 2). Other co-culture products include the metabolites ethylene, isoprene, 3-hydroxypropionic acid (3-HP), and 2,3-butanediol (Table 2), which are compounds in a broader class of industrially relevant precursors widely used for chemical synthesis (e.g., diols, organic acids, gaseous alkenes; Cui et al, 2022;Li C. et al, 2022;Ma et al, 2022).…”
Section: Cyanobacterial Co-culture As a Flexible Platform For Value-a...mentioning
confidence: 99%
See 2 more Smart Citations
“…Francis (2016 10.3389/fmicb.2023.1126032 Frontiers in Microbiology 15 frontiersin.org modest (Löwe et al, 2017;Fedeson et al, 2020). Additional expression of a sucrose porin (cscY) and a sucrose operon repressor (cscR) further improved sucrose utilization (Löwe et al, 2020), while further optimization of the nitrogen-deficiency response pathway (Hobmeier et al, 2020) and culture conditions could boost PHA titer further (Kratzl et al, 2023; Table 2). Other co-culture products include the metabolites ethylene, isoprene, 3-hydroxypropionic acid (3-HP), and 2,3-butanediol (Table 2), which are compounds in a broader class of industrially relevant precursors widely used for chemical synthesis (e.g., diols, organic acids, gaseous alkenes; Cui et al, 2022;Li C. et al, 2022;Ma et al, 2022).…”
Section: Cyanobacterial Co-culture As a Flexible Platform For Value-a...mentioning
confidence: 99%
“…Indeed, initial reports demonstrated that P. putida expressing cscAB was capable of growing solely on sucrose provided by S. elongatus PCC 7942 and accumulated PHA in co-culture, though sucrose utilization was incomplete and productivities were modest ( Löwe et al, 2017 ; Fedeson et al, 2020 ). Additional expression of a sucrose porin ( cscY ) and a sucrose operon repressor ( cscR ) further improved sucrose utilization ( Löwe et al, 2020 ), while further optimization of the nitrogen-deficiency response pathway ( Hobmeier et al, 2020 ) and culture conditions could boost PHA titer further ( Kratzl et al, 2023 ; Table 2 ).…”
Section: Applications Of Sucrose Production In Cyanobacterial Co-culturementioning
confidence: 99%
See 1 more Smart Citation
“…Once co-cultured with cyanobacteria, the microbial PHA producer will be benefited from the oxygen generated from photosynthesis. The microbial consortia containing sucrosesecreting S. elongatus and PHA producer P. putida were constructed for PHA production [26][27][28].…”
Section: Consortia For Wastewater Treatmentmentioning
confidence: 99%
“…, where an engineered P. putida capable of efficiently utilizing sucrose was used [28]. In addition, another engineered P. putida capable of degrading 2,4-dinitrotoluene was used in microbial consortia, allowing simultaneous removal of 2,4-dinitrotoluene and accumulation of PHA from CO2 and light [27].…”
Section: Consortia For Wastewater Treatmentmentioning
confidence: 99%